SAT0178 HYDROXYCHLOROQUINE CONTROLS DISEASE ACTIVITY IN SLE AND MULTIMODAL IMAGING TECHNIQUES SHOULD BE USED TO DETECT OCULAR TOXICITY. (2nd June 2020) - Ince, B.; Ogurel, M. B.; Cebeci, Z.; Tor, Y. B.; Ucar, B. H.; Yalçinkaya, Y.; Gül, A.; Inanc, M.; Ocal, M. L.; Artim-Esen, B.
Abstract : Background: Hydroxychloroquine (HCQ) is an immunomodulatory drug that has been shown to improve disease activity in systemic lupus erythematosus (SLE). However, retinal toxicity is an important concern. Objectives: In this study we sought to evaluate the effect of HCQ on disease activity and damage in patients with SLE in whom HCQ was discontinued due to retinal toxicity and whether it could be restarted by a detailed ophthalmologic examination. Methods: Patients who met SLE SLICC classification criteria and were on HCQ for at least 3 years after reaching Lupus Low Disease Activity State (LLDAS) following remission induction and were followed up for at least 3 years after termination of HCQ treatment due to retinal toxicity diagnosed with visual field test were analyzed. Disease activity (LLDAS and SLEDAI-2K) and both the number and severity of flares were recorded for each patient whilst on HCQ and after cessation of treatment. All patients were examined by two experienced ophthalmologists and were assessed by computerized visual field, optical coherence tomography (OCT), fundus autofluorescence (FAF) and fundus florescein angiography (FFA) to further analyze toxicity. Results: Out of 88 patients with recorded HCQ retinal toxicity in a cohort of 1500 patients with SLE, 64 patients (mean age at diagnosis 33.4 ± 10.5 (10-57); 88.5% female) with complete data and opthalmologic re-examination results were included in the analyses. The average duration on HCQ was 122 ±85 (39-336) months, and the mean follow-up time was 74.6 ± 48.3 (36-239) months after the drug was discontinued. Comparison of mean disease activity in the 3-year period when patients were on HCQ to 3 years post-cessation revealed a significantly lower mean SLEDAI-2K score in the former (0.89±1.28 vs.1.3±1.6, p=0.02). The % of visits maintaining LLDAS was higher during HCQ treatment (89.7 ± 17.6 vs. 80.1 ± 23.5, p=0.001). There was significantly a higher frequency of flares with a dominance of mild-moderate types after HCQ was ceased (47.5 vs. 26.2%, p=0.03; 39.3 vs. 22.9%, p=0.024 respectively). There were more patients with serious flares in the post-discontinuation period but without statistical significance (13.1% vs. 4.9% p=0.08). Thirty-seven (60%) of patients restarted the treatment after ophthalmological examination. Although 38 (62, 3%) patients had visual field defects in the latest examination, multimodal imaging with OCT, FAF and FFA revealed that only 19 (31%) patient had typical retinal toxicity. Five patients were found to have macular atrophy due to other causes (4 age related macular degeneration and 1 vitromacular adhesion). Since the discrimination of macular pathology would not be possible with imaging in these patients, HCQ was not prescribed. Comparison of patients with and without retinal toxicity showed that duration of HCQ use and HCQ-free time was not significantly different between patients. Conclusion: HCQ is effective in controlling disease activity in patients with SLE and an opportunity for re-medication with HCQ is valuable. More than half of the patients being able to restart HCQ after ophthalmologic examination in this study shows that it is important to perform multimodal imaging techniques in patients with retinal toxicity diagnosis. Since macular pathology can have a different etiologic background, an initial opthalmologic examination is also necessary. Lack of difference in the duration of HCQ exposure and drug-free time between patients who restarted treatment and who could not may be a sign of personal sensitivity to HCQ toxicity. Disclosure of Interests: None declared